The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12974-022-02412-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of S100B/RAGE-enhanced ADAM17 activation in endothelial glycocalyx shedding after traumatic brain injury

Abstract: Background Traumatic brain injury (TBI) remains one of the main causes for disability and death worldwide. While the primary mechanical injury cannot be avoided, the prevention of secondary injury is the focus of TBI research. Present study aimed to elucidate the effects and mechanisms of S100B and its receptor RAGE on mediating secondary injury after TBI. Methods This study established TBI animal model by fluid percussion injury in rats, cell mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…The cleavage and release of substrates (inflammatory cytokines, growth factors, receptors, adhesion molecules, and others) for ADAM17 may result in different functions of substrate proteins. Some substrate proteins, such as glycocalyx (104), TNFR (173,178), and JAM-A/FIIR (156), are shed by ADAM17 in the form of active molecules. Glycocalyx is a polysaccharide protein complex that covers the aperture membrane surface of vascular endothelial cells and regulates the homeostasis of the cytoplasmic membrane through proteoglycan-glycoprotein attachment to endothelial cells.…”
Section: Adam17 Mediates Substrate Shedding Activitymentioning
confidence: 99%
“…The cleavage and release of substrates (inflammatory cytokines, growth factors, receptors, adhesion molecules, and others) for ADAM17 may result in different functions of substrate proteins. Some substrate proteins, such as glycocalyx (104), TNFR (173,178), and JAM-A/FIIR (156), are shed by ADAM17 in the form of active molecules. Glycocalyx is a polysaccharide protein complex that covers the aperture membrane surface of vascular endothelial cells and regulates the homeostasis of the cytoplasmic membrane through proteoglycan-glycoprotein attachment to endothelial cells.…”
Section: Adam17 Mediates Substrate Shedding Activitymentioning
confidence: 99%
“…Secreted HMGB1 binds to its receptors RAGE, TLR2, and TLR4 to activate downstream signaling pathways and release in ammatory factors that lead to further damage (Rauvala and Rouhiainen, 2007). Numerous studies have demonstrated that genetic or pharmacological inhibition of RAGE in animal models attenuate brain edema after injury and inhibit pro-in ammatory response (Postolache et al, 2020;Zou et al, 2022). Thus, we studied whether RAGE was involved in TSO IIA-mediated reduction of astrocyte swelling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been correlated with injury severity in hospitalized human patients (Hendoui et al, 2013). High levels of S100B can stimulate inflammatory injury ( Reali et al, 2005 ; Zou et al, 2022 ). S100 B has cytokine-like activities and can interact with the receptor for the advanced glycation end product (RAGE) ( Mori et al, 2008 ; Zou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of S100B can stimulate inflammatory injury ( Reali et al, 2005 ; Zou et al, 2022 ). S100 B has cytokine-like activities and can interact with the receptor for the advanced glycation end product (RAGE) ( Mori et al, 2008 ; Zou et al, 2022 ). Therefore, the decreased concentration of S100B observed in the DMSO-treated rats could be due to its antioxidative effect.…”
Section: Discussionmentioning
confidence: 99%